PERLAKUAN AKUNTANSI BERDASARKAN PENERAPAN ENTITAS TANPA AKUNTABILITAS PUBLIK (ETAP) DALAM MENUNJANG KEWAJARAN LAPORAN KEUANGAN UD. X DI BALI - Clara Sarchan Indrawan; Eko Pudjolaksono (CALYPTRA, 2018)
Abstract - Most SMEs still have problems in terms of lack of knowledge regarding accounting and laziness SMEs to prepare financial statements in accordance with SAK ETAP because it is satisfied with his business and had had enough financial information to improvise in his business. The condition also occurs at UD. X, an SME that is engaged in electronic equipment distributor located in Bali. Although UD.X has long been established and have adequate business activities but has not been able to follow SAK ETAP well in the presentation of financial statements. This study used a qualitative approach to applied research method for this study can be applied by UD.X to improve the fairness of financial statements. From the results of the study authors found that there are some who have not UD.X accounting treatment in accordance with SAK ETAP is the accounting treatment of inventory, fixed assets, income taxes, and the complete financial statements are based SAK ETAP.